"Go NZ YAS!!": Children's news media texts as curriculum resources in Aotearoa New Zealand. (December 2019) - Gunn, Alexandra C; Surtees, Nicola
Attending to current affairs and news within schools' curricula is a potential pedagogical strategy that holds promise for addressing children's knowledge, perspectives and agency in the world. However, our research suggests teachers' good intentions may be compromised by tension between the details of news media content and the curriculum as enacted and planned. We report here on a study investigating two children's news media publications designed to support Aotearoa New Zealand's school curriculum. Our research enquires into content produced as children's news and associated discourses about Aotearoa New Zealand, Aotearoa New Zealand life and the world. A dominant category of news reporting in the texts was sport (national and international). Analysis of this category identified particular discourses and constructions of New Zealand, New Zealanders and 'others' within the texts. Individual and collective sporting heroism was a dominant discourse in both the news items and children's published responses. Furthermore, a construction of Aotearoa New Zealand as a relatively safe and non-corrupt place to live was also observed. Questions of what is important to know, how children are engaging with such valued knowledge and implications for teaching and teachers' practices are raised from this research. Importantly, we ask: is this preoccupation with sports and heroism within children's news made at the expense of opportunities to engage with children about a fuller range of real-world issues, including 'difficult knowledge', that potentially impact upon their lives?